Structure, optical, electrical and thermoelectric properties of solution-processed Li-doped NiO films grown by SILAR - Klochko, N. P.; Klepikova, K. S.; Zhadan, D. O.; Petrushenko, S. I.; Kopach, V. R.; Khrypunov, G. S.; Lyubov, V. M.; Dukarov, S. V.; Nikitin, V. O.; Maslak, M. O.; Zakovorotniy, A.; Khrypunova, A. L. (Elsevier Ltd, 2018)
The article presents a new facial synthesis of Li-doped NiO films (NiO:Li) via an easy and cost-effective method Successive Ionic Layer Adsorption and Reaction (SILAR) with the processing of the obtained NiO films in a lithium-containing aqueous solution for their transformation after annealing into NiO:Li layers. Comparative analysis of crystal structure, optical, electrical and thermoelectric properties of the obtained NiO and NiO:Li 420-1050 nm thick films have reveiled a cubic rock-salt NiO structure, at that, NiO:Li samples are nanocrystalline single phased Li-NiO solid solutions. The fabricated NiO and NiO:Li films are p-type semiconductors with activation energy Ea = 0.1 eV and Ea = 0.25‒0.31 eV, respectively. The obtained in-plane Seebeck coefficients Z are in the range 0.20–0.33 mV/К. Notwithstanding the fact that the maximum values of the thermoelectric power factors P=2.2 μW/K2·m, are rather small, they were achieved if the hot end of the NiO:Li film was heated only to 115 °C. Thus, the produced in this work new low cost thermoelectric thin film material is suitable for a production of electrical energy for low-power devices due to absorption of low-potential heat.
Keywords: Li-doped NiO; SILAR; thermoelectric; resistivity; crystal structure; optical property